Magnitude of Diabetes Mellitus and Associated Factors Among HIV-Infected Individuals on Follow-Up Care at Kuyu General Hospital, North Shoa, Oromia, Ethiopia - Sahilu Tesfaye Weyessa; Eyoel Berhan Mekonen; Tesfalem Teshome Tessema (Journal of Nutrition and Metabolism)
Conclusions: In this study, the magnitude of DM among HIV-infected adults on ART follow-up was higher than the prevalence of DM in general populations. Older age, hypertension, increased total cholesterol, and duration of HIV were associated with a higher prevalence of DM. It is better for care providers assigned at ART clinics to detect DM, particularly after initiation of ART routinely, which may help to provide integrated care for comorbid patients.